2018
DOI: 10.1186/s12871-018-0655-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time delay and body temperature on measurements of central venous oxygen saturation, venous-arterial blood carbon dioxide partial pressures difference, venous-arterial blood carbon dioxide partial pressures difference/arterial-venous oxygen difference ratio and lactate

Abstract: BackgroundCentral venous oxygen saturation (ScvO2), venous-arterial blood carbon dioxide partial pressures difference (Pv-aCO2), venous-arterial blood carbon dioxide partial pressures difference/arterial-venous oxygen difference ratio (Pv-aCO2/Ca-vO2) and lactate are important parameters employed during shock resuscitation. We designed this study to confirm the effects of time delay and body temperature on measurements of these four parameters.MethodsArterial and central venous blood samples were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, available studies involving other populations were only performed for up to 60 min and were not adequate for comparisons with our data. [16][17][18] In general, reductions in mtCO 2 concentrations in the enzymatic assay throughout the experiment were small. The median absolute reduction at the end of the experiment (aliquots analyzed after 24 h of collection) were 1.77, 1.21, 1.04, and 1.12 mmol/L for the non-centrifuged/nonrefrigerated, centrifuged/non-refrigerated, non-centrifuged/ refrigerated, and centrifuged/refrigerated aliquots, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, available studies involving other populations were only performed for up to 60 min and were not adequate for comparisons with our data. [16][17][18] In general, reductions in mtCO 2 concentrations in the enzymatic assay throughout the experiment were small. The median absolute reduction at the end of the experiment (aliquots analyzed after 24 h of collection) were 1.77, 1.21, 1.04, and 1.12 mmol/L for the non-centrifuged/nonrefrigerated, centrifuged/non-refrigerated, non-centrifuged/ refrigerated, and centrifuged/refrigerated aliquots, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, such patients are not expected to behave differently from other patients in general. However, available studies involving other populations were only performed for up to 60 min and were not adequate for comparisons with our data 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…We tested all the samples within 60 min, because it is recognized that the concentration of blood gases significantly changes after this time ( Mohammadhoseini et al, 2015 ; Wan et al, 2018 ). Furthermore, the i-STAT1 manufacturer recommends testing blood samples with the CG8+ cartridge within 10 min of collection ( Abbott Point of Care Inc., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies. Mekontso-Dessap A et al found that the Pv-aCO2 /Ca − vO2 ratio could detect global anaerobic metabolism in critically ill patients (28). As an index of the presence of anaerobic metabolism, its basic theory is:…”
Section: Discussionmentioning
confidence: 99%